Classification of peripheral vitreoretinal interface lesions using spectral-domain optical coherence tomography with guidance of ultrawide field imaging - Zheng, Weiwei; Huang, Ying; Qian, Shanshan; Lin, Bing; Huang, Shenghai (Frontiers in Neuroscience, 2025)
PurposeThis study aimed to classify peripheral vitreoretinal interface (VRI) lesions using optical coherence tomography (OCT) and to compare these findings with those obtained by ultra-widefield (UWF) pseudocolor imaging.MethodPeripheral OCT images of VRI lesions were obtained using spectral domain OCT system with a steerable probe guided by UWF images. Two independent investigators categorized the OCT images into four groups based on the extent of vitreoretinal traction and the presence of retinal breaks. Differences in OCT-based categorization between the same lesion types visualized by UWF imaging were also compared.ResultsOf the total 82 patients, 105 peripheral lesions were included in this study. The inter-observer agreement for the classification of UWF and OCT images demonstrated good consistency, with kappa values of 0.949 ± 0.025 and 0.836 ± 0.042, respectively. In the OCT classification of VRI lesions, 18 (17.1%) cases were category A, 28 (26.7%) cases were category B1, 30 (28.6%) cases were category B2, and 29 (27.6%) cases were category C. Of the 37 vitreoretinal tuft lesions, 32.4% were classified as category B2 and 16.2% as category C, according to peripheral OCT classification. Similarly, 37.8% of 40 snail track and lattice degeneration lesions were classified as category B2, and 16.2% as category C.ConclusionThe VRI lesions can demonstrate considerable variability when visualized with peripheral OCT among the same lesion types visualized through UWF imaging. Classification of peripheral OCT images may provide a more effective evaluation of the risk of lesion progression.